A compact miniature fractal planar antenna for RFID readers - Mohamed Ihamji; Elhassane Abdelmounim; Jamal Zbitou; Hamid Bennis; Mohamed Latrach (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This article presents a new miniature microstrip antenna in the ISM "Industrial Scientific and Medical" band, at 2.45 GHz. This microstrip antenna is designed for RFID reader system, by exploiting the fractal technique and the CPW fed; this antenna is printed on FR4 substrate with dielectric constant of 4.4. The validated antenna has a good matching input impedance range from 2.27 GHz to 2.68 GHz with a stable radiation pattern, a gain of 2.2 dBi, and a directivity of 1.91 dB. The total area of the final circuit is 21.22 x 32.05 mm2. A prototype of the proposed antenna has been fabricated and measured.